Green low-carbon recycled concrete for cold regions and preparation method of green low-carbon recycled concrete

By adding silicone and polyvinyl alcohol fibers to the recycled concrete and combining the technology of modifying regenerated coarse aggregates, the problems of unstable mechanical properties and poor durability of regenerated concrete when used in cold areas are solved, and higher mechanical properties and long-term performance are achieved.

CN119613041APending Publication Date: 2025-03-14SHAANXI HENGSHENG GREEN CONSTRUCTION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411743647.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When used in cold areas, existing recycled concrete has problems such as unstable mechanical properties, poor durability and prone to cracking, which affects the safety and service life of the building.

Method used

By adding silicone and polyvinyl alcohol fibers to the mix ratio of recycled concrete, further hydration of unhydrated cement particles is promoted, pores inside the cement base are reduced, and density and durability are enhanced. At the same time, the regenerated aggregate is modified and regenerated by soaking nano SiO2 to improve the bonding between the old cement mortar and the aggregate.

Benefits of technology

It significantly improves the mechanical properties and long-term properties of recycled concrete, solves the problem of inability to take into account both durability and mechanical properties, and is suitable for building materials in cold areas.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses green low-carbon recycled concrete for a cold region. The recycled concrete is prepared from the following components in parts by weight: 300 to 350 parts of cement, 100 to 120 parts of fly ash, 356 to 1040 parts of recycled coarse aggregate, 0 to 5 parts of polyvinyl alcohol fiber, 0 to 15 parts of organic silicon, 4.8 to 8 parts of polycarboxylate superplasticizer, 0.12 to 0.24 part of air entraining agent, 0 to 680 parts of natural coarse aggregate, 620 to 815 parts of natural fine aggregate and 135 to 150 parts of water, the invention further discloses a preparation method of the recycled concrete. The organic silicon is added into the recycled concrete to promote hydration of unhydrated cement particles in the concrete, so that internal pores of a cement base are reduced, the compactness of the recycled concrete is enhanced, the durability and the mechanical property are improved, and the recycled concrete is suitable for the technical field of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to green low-carbon recycled concrete for cold regions and a preparation method thereof. Background Art

[0002] Concrete is a common building material, but there are problems such as high carbon emissions and low resource utilization in the production process. In order to reduce the adverse impact of concrete production on the environment and improve resource utilization, recycled concrete is usually prepared using waste concrete as raw material. Not only can it reduce the production of building materials and avoid the high carbon dioxide produced in certain links, but recycled concrete can also fix carbon through carbonization reaction with carbon dioxide, which plays a very important role in promoting the realization of carbon peak and carbon neutrality goals.

[0003] However, due to the quality of recycled coarse aggregate, recycled concrete has problems such as unstable mechanical properties, poor working performance, and easy cracking in the later stage. For example, the Chinese invention patent "A Recycled Concrete" (Announcement No. CN106927756B) is composed of cementitious materials, coarse aggregate, fine aggregate, recycled modified PET plastic particles, admixtures, natural river sand and water, which improves the problems of poor impermeability and durability of recycled concrete in the prior art; but its mechanical properties have not been improved, especially in the cold and dry environment in the north, it is more prone to cracking, corrosion and other problems, affecting the safety and service life of the building.

[0004] Therefore, how to ensure that the mechanical properties and workability of recycled concrete are effectively improved while ensuring good durability is a problem that needs to be solved. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a green low-carbon recycled concrete for cold regions. The recycled concrete can promote the further hydration of unhydrated cement particles in the concrete by adding organosilicon in the mix ratio, significantly reduce the pores inside the cement base, thereby enhancing the internal density of the recycled concrete and improving the durability of the recycled concrete; by adding polyvinyl alcohol fiber and organosilicon to work synergistically, the organosilicon can form numerous hydrogen bonds to improve the interaction between the polyvinyl alcohol fiber and cement, and improve the weak interface between the new and old cements through stable chemical bonds, thereby improving the mechanical properties and long-term performance of the recycled concrete, solving the problem that the durability and mechanical properties of the recycled concrete in the prior art cannot be taken into account at the same time.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a green and low-carbon recycled concrete for cold areas, characterized in that the recycled concrete comprises the following components in parts by weight: 300-350 parts of cement, 100-120 parts of fly ash, 356-1040 parts of recycled coarse aggregate, 0-5 parts of polyvinyl alcohol fiber, 0-15 parts of organosilicon, 4.8-8 parts of polycarboxylic acid water reducer, 0.12-0.24 parts of air entraining agent, 0-680 parts of natural coarse aggregate, 620-815 parts of natural fine aggregate, and 135-150 parts of water.

[0007] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the cement is 42.5 grade ordinary Portland cement and the fly ash is grade II fly ash.

[0008] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the recycled coarse aggregate is modified recycled coarse aggregate, and the preparation process of the modified recycled coarse aggregate is: placing the recycled coarse aggregate in a nano-SiO 2 The modified solution is treated for 12 to 48 hours, and then filtered, air-dried, and sieved. The recycled coarse aggregate particles in different particle size ranges after sieving are mixed to obtain modified recycled coarse aggregate with a continuous gradation of 5 mm to 25 mm in particle size.

[0009] The present invention adopts the method of soaking nano-SiO 2 The recycled coarse aggregate was modified by nano-SiO 2 It can penetrate into the surface of recycled coarse aggregate several microns below the surface, filling the pores and micro cracks of recycled coarse aggregate; at the same time, in the old interface transition zone between recycled coarse aggregate and mortar, nano-SiO 2 With Ca(OH) 2 React to form CSH gel, promote the formation of a tighter interface transition zone, improve the bonding between old cement mortar and aggregate, and thus improve the durability of recycled concrete;

[0010] In addition, the surface of the modified recycled coarse aggregate also has deposited nano-SiO 2 During the mixing process of concrete preparation, organic silicon can 2 The modified recycled coarse aggregate is modified so that the modified recycled coarse aggregate is grafted with the polyvinyl alcohol fiber, the bonding force between the polyvinyl alcohol fiber and the modified recycled coarse aggregate is improved, and then the interface bonding between the modified recycled coarse aggregate and the cement matrix and the density of the recycled concrete are improved.

[0011] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the particle size of the recycled coarse aggregate is 5mm to 25mm, and the apparent density is 2600kg / m 3 ~2680kg / m 3The natural coarse aggregate has a particle size of 5 mm to 25 mm and an apparent density of 2550 kg / m 3 ~2610kg / m 3 ; The natural fine aggregate is river sand with a fineness modulus of 2.5 to 2.7.

[0012] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the diameter of the polyvinyl alcohol fiber is 32μm to 38μm, and the length of the polyvinyl alcohol fiber is 10mm to 13mm.

[0013] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the organic silicon is a silane coupling agent KH560.

[0014] The above-mentioned green low-carbon recycled concrete for cold regions is characterized in that the air entraining agent includes the following components in parts by weight: 50-60 parts of rosin powder, 1-5 parts of triterpenoid saponin, 5-10 parts of sodium hydroxide, 4-8 parts of sulfuric acid, and 10-20 parts of ethylene glycol, and the mass concentration of the sulfuric acid is 20% to 40%.

[0015] In addition, the present invention also discloses a method for preparing the green low-carbon recycled concrete for cold regions, which is characterized in that the method comprises the following steps:

[0016] Step 1: Weigh cement, fly ash, water, fine aggregate, natural coarse aggregate, recycled coarse aggregate, polyvinyl alcohol fiber, organosilicon, polycarboxylic acid high-performance water reducing agent and air entraining agent according to the mix ratio;

[0017] Step 2: Add the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and stir evenly; then evenly disperse the polyvinyl alcohol fiber weighed in step 1 and add it to stir; finally, sequentially add the organosilicon, water, polycarboxylic acid high-performance water-reducing agent and air-entraining agent weighed in step 1 into the mixer and stir to obtain recycled concrete.

[0018] The invention firstly mixes recycled coarse aggregate, cement, fly ash, natural coarse aggregate and fine aggregate evenly, then adds polyvinyl alcohol fiber separately to make the polyvinyl alcohol fiber evenly dispersed, and finally adds organosilicon, water, polycarboxylic acid high-performance water reducing agent and air entraining agent for mixing, thereby ensuring that each component is evenly distributed in the concrete.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The present invention can promote further hydration of unhydrated cement particles in concrete by adding organosilicon to the mix ratio of recycled concrete, significantly reduce the pores inside the cement base, thereby enhancing the internal density of the recycled concrete and improving the durability of the recycled concrete; by adding polyvinyl alcohol fiber and organosilicon for synergistic effect, the organosilicon can form numerous hydrogen bonds to improve the interaction between polyvinyl alcohol fiber and cement, and improve the weak interface between new and old cement through stable chemical bonds, thereby improving the mechanical properties and long-term performance of the recycled concrete.

[0021] 2. The present invention adopts recycled coarse aggregate instead of natural aggregate, which reduces the consumption of natural aggregate on the one hand, and on the other hand, the use of recycled coarse aggregate can greatly reduce the carbon emissions of recycled concrete throughout its life cycle, reduce environmental pollution, and reduce production costs.

[0022] 3. The present invention adopts the method of soaking nano-SiO 2 Modifying the recycled coarse aggregate in this way can improve the density of the modified recycled coarse aggregate itself, improve the bonding between the old cement mortar and the modified recycled coarse aggregate and the density of the recycled concrete, thereby improving the durability of the recycled concrete.

[0023] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0024] The cement used in Examples 1 to 4 is all 42.5 grade ordinary Portland cement, with a median particle size (D50) of 14.45 μm; the fly ash is all Grade II fly ash, with a median particle size (D50) of 20.42 μm, and a water requirement of 102%; the continuous grading particle sizes of the recycled coarse aggregate and the natural coarse aggregate are all 5 mm to 25 mm, the natural fine aggregate is all river sand, and the organosilicon is all silane coupling agent KH560, with an organosilicon density of 1.060 g / cm 3 The water reducing rate of polycarboxylic acid water reducer is 25%, and the water is tap water.

[0025] Example 1

[0026] The recycled concrete of this embodiment includes the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 520 parts of modified recycled coarse aggregate, 0 parts of polyvinyl alcohol fiber, 5 parts of silane coupling agent KH560, 4.8 parts of polycarboxylic acid water reducer, 0.12 parts of air entraining agent, 520 parts of natural coarse aggregate, 720 parts of natural fine aggregate, and 150 parts of water; the air entraining agent includes the following components in parts by weight: 50 parts of rosin powder, 5 parts of triterpenoid saponin, 10 parts of sodium hydroxide, 4 parts of sulfuric acid, and 10 parts of ethylene glycol, and the mass concentration of the sulfuric acid is 40%; the diameter of the polyvinyl alcohol fiber is 37 μm, and the length of the polyvinyl alcohol fiber is 12 mm; the apparent density of the recycled coarse aggregate is 2600 kg / m 3The apparent density of the natural coarse aggregate is 2610kg / m 3 ; The fineness modulus of the natural fine aggregate is 2.7.

[0027] The preparation method of this embodiment comprises the following steps:

[0028] Step 1: Place the recycled coarse aggregate in a 1% mass concentration of nano-SiO 2 Soaking in the solution for 48 hours, then filtering, air-drying, and sieving, mixing the recycled coarse aggregate particles of different particle size ranges after sieving, and obtaining modified recycled coarse aggregate with a particle size of 5 mm to 25 mm and continuous gradation;

[0029] According to the mix ratio, weigh 300 parts of cement, 100 parts of fly ash, 150 parts of water, 720 parts of natural fine aggregate, 520 parts of natural coarse aggregate, 520 parts of modified recycled coarse aggregate, 5 parts of silane coupling agent KH560, 4.8 parts of polycarboxylic acid high-performance water reducing agent and 0.12 parts of air entraining agent;

[0030] Step 2: Add the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and mix them evenly, then add the silane coupling agent KH560, water, polycarboxylic acid high-performance water reducer and air entraining agent weighed in step 1 into the mixer in sequence and mix to obtain recycled concrete.

[0031] After testing, the recycled concrete of this embodiment has a slump of 90 mm, a 28d compressive strength of 49.5 MPa, and a frost resistance grade of not less than F200.

[0032] Comparative Example 1

[0033] The difference between this comparative example and Example 1 is that the recycled concrete in this comparative example includes the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 0 parts of polyvinyl alcohol fiber, 5 parts of silane coupling agent KH560, 4.8 parts of polycarboxylate water reducer, 0.12 parts of air entraining agent, 1040 parts of natural coarse aggregate, 720 parts of natural fine aggregate, and 150 parts of water.

[0034] After testing, the slump of the recycled concrete in this comparative example is 95 mm, and the 28d compressive strength is 45.5 MPa. Compared with the recycled concrete in Example 1, the strength of the concrete using natural coarse aggregate in this comparative example is not much different from that of the recycled concrete in Example 1, indicating that the modified recycled coarse aggregate of the present invention has excellent performance and can replace natural coarse aggregate to prepare concrete.

[0035] Example 2

[0036] The recycled concrete of this embodiment includes the following components in parts by weight: 310 parts of cement, 100 parts of fly ash, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 5.2 parts of polycarboxylic acid water reducer, 0.123 parts of air entraining agent, 520 parts of natural coarse aggregate, 720 parts of natural fine aggregate, and 150 parts of water; the air entraining agent includes the following components in parts by weight: 60 parts of rosin powder, 1 part of triterpenoid saponin, 7 parts of sodium hydroxide, 6 parts of sulfuric acid, and 15 parts of ethylene glycol, and the mass concentration of the sulfuric acid is 30%; the diameter of the polyvinyl alcohol fiber is 32 μm, and the length of the polyvinyl alcohol fiber is 10 mm; the apparent density of the recycled coarse aggregate is 2620 kg / m 3 The apparent density of the natural coarse aggregate is 2600kg / m 3 ; The fineness modulus of the natural fine aggregate is 2.6.

[0037] The preparation method of this embodiment comprises the following steps:

[0038] Step 1: Place the recycled coarse aggregate in a 2% mass concentration of nano-SiO 2 Soaking in the solution for 48 hours, then filtering, air-drying, and sieving, mixing the recycled coarse aggregate particles of different particle size ranges after sieving, and obtaining modified recycled coarse aggregate with a particle size of 5 mm to 25 mm and continuous gradation;

[0039] According to the mix ratio, weigh 310 parts of cement, 100 parts of fly ash, 150 parts of water, 720 parts of natural fine aggregate, 520 parts of natural coarse aggregate, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 5.2 parts of polycarboxylic acid high-performance water reducing agent and 0.123 parts of air entraining agent;

[0040] Step 2: Put the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and stir evenly, then evenly disperse the polyvinyl alcohol fiber weighed in step 1 and add it to stir for 2.5 minutes, finally, add the silane coupling agent KH560, water, polycarboxylic acid high-performance water reducer and air entraining agent weighed in step 1 into the mixer in turn and stir to obtain recycled concrete.

[0041] After testing, the recycled concrete of this embodiment has a slump of 82 mm, a 28d compressive strength of 40.3 MPa, and a frost resistance grade of not less than F200.

[0042] Example 3

[0043] The recycled concrete of this embodiment includes the following components in parts by weight: 320 parts of cement, 110 parts of fly ash, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 10 parts of silane coupling agent KH560, 6.5 parts of polycarboxylic acid water reducer, 0.172 parts of air entraining agent, 520 parts of natural coarse aggregate, 780 parts of natural fine aggregate, and 145 parts of water; the air entraining agent includes the following components in parts by weight: 55 parts of rosin powder, 3 parts of triterpenoid saponin, 8 parts of sodium hydroxide, 8 parts of sulfuric acid, and 20 parts of ethylene glycol, and the mass concentration of the sulfuric acid is 20%; the diameter of the polyvinyl alcohol fiber is 38 μm, and the length of the polyvinyl alcohol fiber is 11 mm; the apparent density of the recycled coarse aggregate is 2680 kg / m 3 The apparent density of the natural coarse aggregate is 2550kg / m 3 ; The fineness modulus of the natural fine aggregate is 2.5.

[0044] The preparation method of this embodiment comprises the following steps:

[0045] Step 1: Place the recycled coarse aggregate in a 3% mass concentration of nano-SiO 2 Soaking in the solution for 48 hours, then filtering, air-drying, and sieving, mixing the recycled coarse aggregate particles of different particle size ranges after sieving, and obtaining modified recycled coarse aggregate with a particle size of 5 mm to 25 mm and continuous gradation;

[0046] According to the mix ratio, weigh 320 parts of cement, 110 parts of fly ash, 145 parts of water, 780 parts of natural fine aggregate, 520 parts of natural coarse aggregate, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 10 parts of silane coupling agent KH560, 6.5 parts of polycarboxylic acid high-performance water reducing agent and 0.172 parts of air entraining agent;

[0047] Step 2: Add the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and stir evenly, then evenly disperse the polyvinyl alcohol fiber weighed in step 1 and add it to stir for 2 minutes, finally, add the silane coupling agent KH560, water, polycarboxylic acid high-performance water reducer and air entraining agent weighed in step 1 into the mixer in turn and stir to obtain recycled concrete.

[0048] After testing, the recycled concrete of this embodiment has a slump of 85 mm, a 28d compressive strength of 54.2 MPa, and a frost resistance grade of not less than F200.

[0049] Example 4

[0050] The recycled concrete of this embodiment includes the following components in parts by weight: 350 parts of cement, 120 parts of fly ash, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 15 parts of silane coupling agent KH560, 8 parts of polycarboxylic acid water reducer, 0.235 parts of air entraining agent, 520 parts of natural coarse aggregate, 815 parts of natural fine aggregate, and 145 parts of water; the air entraining agent includes the following components in parts by weight: 52 parts of rosin powder, 4 parts of triterpenoid saponin, 6 parts of sodium hydroxide, 5 parts of sulfuric acid, and 14 parts of ethylene glycol, and the mass concentration of the sulfuric acid is 35%; the diameter of the polyvinyl alcohol fiber is 36 μm, and the length of the polyvinyl alcohol fiber is 13 mm; the apparent density of the recycled coarse aggregate is 2650 kg / m 3 The apparent density of the natural coarse aggregate is 2600kg / m 3 ; The fineness modulus of the natural fine aggregate is 2.7.

[0051] The preparation method of this embodiment comprises the following steps:

[0052] Step 1: Place the recycled coarse aggregate in a 3% mass concentration of nano-SiO 2 Soaking in the solution for 48 hours, then filtering, air-drying, and sieving, mixing the recycled coarse aggregate particles of different particle size ranges after sieving, and obtaining modified recycled coarse aggregate with a particle size of 5 mm to 25 mm and continuous gradation;

[0053] According to the mix ratio, weigh 350 parts of cement, 120 parts of fly ash, 145 parts of water, 815 parts of natural fine aggregate, 520 parts of natural coarse aggregate, 520 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 15 parts of silane coupling agent KH560, 8 parts of polycarboxylic acid high-performance water reducing agent and 0.235 parts of air entraining agent;

[0054] Step 2: Add the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and stir evenly, then evenly disperse the polyvinyl alcohol fiber weighed in step 1 and add it to stir for 3 minutes, finally, add the silane coupling agent KH560, water, polycarboxylic acid high-performance water reducer and air entraining agent weighed in step 1 into the mixer in turn and stir to obtain recycled concrete.

[0055] After testing, the recycled concrete of this embodiment has a slump of 87 mm, a 28d compressive strength of 57.4 MPa, and a frost resistance grade of not less than F200.

[0056] Example 5

[0057] The difference between this embodiment and embodiment 4 is that: in step 1, the recycled coarse aggregate is 2 Soak in the solution for 12 hours.

[0058] According to the test, the 28d compressive strength of the recycled concrete in this embodiment is 56.0MPa, and the frost resistance grade is not less than F200.

[0059] Example 6

[0060] The difference between this embodiment and embodiment 4 is that the recycled concrete of this embodiment comprises the following components in parts by weight: 350 parts of cement, 120 parts of fly ash, 1040 parts of modified recycled coarse aggregate, 5 parts of polyvinyl alcohol fiber, 15 parts of silane coupling agent KH560, 8 parts of polycarboxylic acid water reducer, 0.235 parts of air entraining agent, 620 parts of natural fine aggregate, and 135 parts of water; in step 1, the recycled coarse aggregate is mixed with nano-SiO 2 Soak in the solution for 36 hours.

[0061] According to the test, the 28d compressive strength of the recycled concrete in this embodiment is 58.2MPa, and the frost resistance grade is not less than F200.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 4 is that the recycled concrete of this embodiment comprises the following components in parts by weight: 350 parts of cement, 120 parts of fly ash, 356 parts of modified recycled coarse aggregate, 4 parts of polyvinyl alcohol fiber, 15 parts of silane coupling agent KH560, 8 parts of polycarboxylic acid water reducer, 0.235 parts of air entraining agent, 680 parts of natural coarse aggregate, 800 parts of natural fine aggregate, and 135 parts of water; in step 1, the recycled coarse aggregate is mixed with nano-SiO 2 Soak in the solution for 30 hours.

[0064] According to the test, the 28d compressive strength of the recycled concrete in this embodiment is 58.5MPa, and the frost resistance grade is not less than F200.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A green low-carbon recycled concrete for cold regions, characterized in that: The recycled concrete comprises the following components in parts by weight: 300-350 parts of cement, 100-120 parts of fly ash, 356-1040 parts of recycled coarse aggregate, 0-5 parts of polyvinyl alcohol fiber, 0-15 parts of organic silicon, 4.8-8 parts of polycarboxylic acid water reducer, 0.12-0.24 parts of air entraining agent, 0-680 parts of natural coarse aggregate, 620-815 parts of natural fine aggregate and 135-150 parts of water.

2. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The cement is 42.5 grade ordinary Portland cement, and the fly ash is grade II fly ash.

3. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The recycled coarse aggregate is a modified recycled coarse aggregate. The preparation process of the modified recycled coarse aggregate is as follows: the recycled coarse aggregate is placed in a nano-SiO2 solution with a mass concentration of 1% to 3% for modification for 12h to 48h, and then filtered, air-dried, and sieved. The recycled coarse aggregate particles with different particle size ranges after sieving are mixed to obtain modified recycled coarse aggregate with a particle size of 5mm to 25mm and continuous grading.

4. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 5mm to 25mm, and the apparent density is 2600kg / m 3 ~2680kg / m 3 The natural coarse aggregate has a particle size of 5 mm to 25 mm and an apparent density of 2550 kg / m 3 ~2610kg / m 3 ; The natural fine aggregate is river sand with a fineness modulus of 2.5 to 2.

7.

5. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The diameter of the polyvinyl alcohol fiber is 32 μm to 38 μm, and the length of the polyvinyl alcohol fiber is 10 mm to 13 mm.

6. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The organosilicon is silane coupling agent KH560.

7. The green low-carbon recycled concrete for cold regions according to claim 1, characterized in that: The air entraining agent comprises the following components in parts by weight: 50-60 parts of rosin powder, 1-5 parts of triterpenoid saponin, 5-10 parts of sodium hydroxide, 4-8 parts of sulfuric acid, and 10-20 parts of ethylene glycol. The mass concentration of the sulfuric acid is 20%-40%.

8. A method for preparing green low-carbon recycled concrete for cold regions as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Step 1: Weigh cement, fly ash, water, fine aggregate, natural coarse aggregate, recycled coarse aggregate, polyvinyl alcohol fiber, organosilicon, polycarboxylic acid high-performance water reducing agent and air entraining agent according to the mix ratio; Step 2: Add the recycled coarse aggregate, cement, fly ash, natural coarse aggregate and natural fine aggregate weighed in step 1 into a mixer and stir evenly; then evenly disperse the polyvinyl alcohol fiber weighed in step 1 and add it to stir; finally, sequentially add the organosilicon, water, polycarboxylic acid high-performance water-reducing agent and air-entraining agent weighed in step 1 into the mixer and stir to obtain recycled concrete.

Citation Information

Patent Citations

  • A type of recycled concrete

    CN106927756B